1976
DOI: 10.1037/0012-1649.12.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Observational learning of quantity conservation and Piagetian generalization tasks.

Abstract: To establish whether data on the social learning of conservation are compatible with Piaget's position, it is important to determine if the observationally acquired conservation meets Piagetian generalization and stability criteria. During a single brief observation period, first-grade children observed the correct performance of an adult model on an easy quantity conservation task. Children were then submitted to a series of generalization tasks on immediate, 1-week, and 3-month delayed posttests. On the whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
4

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 12 publications
1
4
0
4
Order By: Relevance
“…The subjects were sufficiently advanced in symbolic manipula tion and interiorizing action to begin cognitive restructuring in response to a verbal stimulus or vicarious manipulation as easily as from personal action, even though they had not yet acquired the skills of Piaget's concrete operations stage. Similar results were found in a study by Charbonneau et al (1976). Their young, pre-operational subjects responded to observational training in two categories.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The subjects were sufficiently advanced in symbolic manipula tion and interiorizing action to begin cognitive restructuring in response to a verbal stimulus or vicarious manipulation as easily as from personal action, even though they had not yet acquired the skills of Piaget's concrete operations stage. Similar results were found in a study by Charbonneau et al (1976). Their young, pre-operational subjects responded to observational training in two categories.…”
Section: Discussionsupporting
confidence: 88%
“…Research on training young, pre-operational Euro-American children to conserve on Piagetian tasks has found a variety of techniques to be successful. For example, perceptual screening (Bruner 1966), modeling and reversibility cues (Zimmerman and Lanaro 1974), and observa tional learning alone (Charbonneau et al 1976) have all been effective. Working with older children Johnson and Howe (1978) were successful using cognitive conflict promoted by peer interaction.…”
mentioning
confidence: 99%
“…Moreover, a high degree of mastery of these tasks had been obtained among similar samples of observationally trained conservers The 12 conservation tusks were divided into two parts. The first part (Conservation I) involved five 1-2 (Charbonneau et al, 1976;Robert & Charbonneau, 1979) and a pilot study had indicated that the same conclusion held for natural conservers. Equality judgments and explanations were required.…”
Section: Methodsmentioning
confidence: 88%
“…Other tasks were also judged to be fairly difficult because they required the child to memorize the product of several transformations (Task 8), to supply inequality judgements and explanations (Task 9) or to predict the outcome of a transformation (Task 10). Furthermore, a moderate mastery of these tasks had been measured among similar samples of observationally trained conservers (Charbonneau et al, 1976;Robert 8t Charbonneau, 1979. For Task 6, B containing 40 cc of liquid, the child had to pour the same amount into A, and D. For Task 7, E, F, B, A,, and G were respectively filled up to heights of 19.5, 19.5, 7, 9.7 and 13.4 cm and the child chose the beaker containing the least amount of liquid, then the next one, and so on, until only one beaker was left.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation